Medicine Optimisation Using PCSK9 Monoclonal Antibodies (alirocumab and evolocumab) Concerning the European Atherosclerosis Society (EAS) of < 1.8 mmol/l LDL Cholesterol Target in a Secondary Care Lipid Clinic - Bolodeoku, John; Gbaa, Terry; Morris, Katherine; Whitehead, Simon (British Journal of Healthcare and Medical Research, 2023)
Proprotein convertase subtilisin kexin type 9 (PCSK9) is an essential regulator of cholesterol metabolism. It was introduced as a monoclonal antibody to regulate LDL-R by recycling more LDLR onto the cell's surface. The clinically available PCSK9 monoclonal antibodies are alirocumab and evolocumab. This audit-based assessment aims to evaluate the impact of PCSK9 inhibitors on patient outcomes in achieving the European Atherosclerosis Society (EAS) recommended target for low-density lipoprotein cholesterol (LDL-C) levels (<1.8mmol/l) within a secondary care lipid clinic.